SURGICAL MANAGEMENT OF CYSTIC ENDOMETRIAL HYPERPLASIA- PYOMETRA COMPLEX WITH UTERINE FIBROADENOMA AND VAGINAL LEIOMYOMA IN A DOG - X, MINU; R S, ABHILASH; JAYAKUMAR, R S; KUMAR , VINAY; P M, SHABEEBA (The Indian Journal of Animal Reproduction, 2021)
A seven-year-old intact German Shepherd bitch was presented to the University Veterinary Hospital, Kokkalai with a complaint of bleeding from the vulva and constipation for the past three months. On general examination, the animal was emaciated, and bleeding was noticed from the vagina. Per vaginal examination revealed the presence of growth in the vaginal cavity. The condition was tentatively diagnosed as cystic endometrial hyperplasia pyometra complex with a mass in the abdominal cavity and vagina. Exploratory laparotomy was performed under general anesthesia and ovariohysterectomy (OHE) was carried out, and episiotomy procedure was performed to remove the vaginal mass. Postoperatively animal was managed with antibiotics and supportive therapies, and the animal made an uneventful recovery, further no recurrence was observed. On histopathological examination of the uterine mass was confirmed as fibroadenoma and vaginal mass as leiomyoma. The present case report suggests that dogs suffering from CEH pyometra along with uterine fibroadenoma and vaginal leiomyoma can be successfully managed with surgical excision of the tumor mass and OHE.